Anti-LGI1 encephalitis with initiating symptom of seizures in children - Wang, Yang; Zhang, Dongqing; Tong, Lili; Yang, Lu; Yin, Ping; Li, Jun; Lei, Gefei; Yang, Xiaofan; Li, Baomin (Frontiers in Neuroscience, 2023)
Background Anti-leucine-rich glioma-inactivated 1 (LGI1) encephalitis is infrequently reported but more and more recognizable in children. Here we give detailed description of the clinical features and long-term outcome of three cases of childhood onset anti-LGI1 encephalitis. Methods Three anti-LGI1 encephalitis patients were hospitalized in the Department of Pediatrics at Qilu Hospital of Shandong University. Data about the clinical manifestations, treatments and long-term follow-up outcomes were described in detail. Results Case 1 showed an adolescent girl with initiating symptom of acute-onset frequent focal seizures. Her serum LGI1-antibody test was positive, and she had a good response to antiseizure medication (ASM) and IVIG. Case 2 showed a preschool-age boy with long-period refractory focal seizures and recent behavioral change. Both serum and cerebrospinal fluid (CSF) tests of LGI1-antibody were positive, and the MRI showed progressive atrophy in the left hemisphere. The symptoms got improved after receiving second-line immunotherapy initially but there are still the sequelae of drug-resistant epilepsy and mild to moderate intellectual disability. Case 3 showed an adolescent boy with initiating symptom of acute-onset frequent focal seizures. Both serum and CSF tests of LGI1-antibody were positive, and he had a good response to immunotherapy. By analyzing all literature-reported 19 pediatric cases, we found pediatric anti-LGI1 encephalitis is more common in female and adolescent. Seizures and behavioral changes were the most common symptoms. CSF pleocytosis and LGI1-antibodies results were mostly negative. Most patients showed good response to immunotherapy. Conclusion Childhood onset anti-LGI1 encephalitis is a heterogeneous clinical syndrome, ranging from typical limbic encephalitis to isolating focal seizures. It is important to test autoimmune antibodies when encountering similar cases and repeat antibody testing if necessary. Timely recognition leads to earlier diagnosis and more rapid initiation of effective immunotherapy and potentially better outcomes.